Oblong cup in the management of aseptic loosening of the acetabular component in total hip replacement - Fousek, J; Vasek, P (Scandinavian journal of surgery, 2007)
BACKGROUND AND AIMS: At present, revision surgery of a total hip replacement is a major problem that must be dealt with by all orthopedic facilities. Aseptic loosening of the acetabular component is often associated with destruction of the original spherical shape of the acetabulum and the formation of bone defects. An orthopedist faces the challenge of acetabular revision and stable fixation of the new acetabular component in an effort to re-establish the functioning of the hip replacement. MATERIAL AND METHODS: The authors evaluated a group of 74 patients in whom they implanted an oblong revision cup due to aseptic loosening of the acetabular component from August 2000 until December 2003. The mean duration of the follow-up period was 63 months (ranging from 38 to 78 months). RESULTS AND CONCLUSIONS: The authors reported very good results from the use of this implant, where osteointegration and good functional outcome evaluated according to the Harris Hip Score (HHS) were achieved in 95% of cases. The long-term outcome should be the subject of further investigation.
Keywords: senioři; náhrada kyčelního kloubu; Prosthesis Design; senioři nad 80 let; reoperace; Arthroplasty, Replacement, Hip; Retrospective Studies; artróza kyčelních kloubů; Osteoarthritis, Hip; Radiography; výsledek terapie; Middle Aged; mužské pohlaví; Adult; Reoperation; Follow-Up Studies; protézy - design; následné studie; Aged, 80 and over; ženské pohlaví; radiografie; retrospektivní studie; Humans; lidé středního věku; Femur Head Necrosis; nekróza hlavice femuru; dospělí; Prostheses and Implants; Female; Aged; Treatment Outcome; lidé; Male; protézy a implantáty